2016
DOI: 10.1109/tcomm.2016.2616136
|View full text |Cite
|
Sign up to set email alerts
|

An Adaptive Transmission Scheme for Amplify-and-Forward Relaying Networks

Abstract: Abstract-In this work, an adaptive scheme for amplify-andforward relaying networks is proposed, which selects a certain transmission mode for each communication process. Depending on the instantaneous channel conditions, one of the following modes is selected: direct transmission with no cooperation, cooperative transmission with half-duplex relaying and maximalratio combining at the destination, or cooperative transmission with full-duplex relaying and maximal-ratio combining at the destination. A three-node … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Fig. 8 illustrates the system sum rate versus the transmit SNR, as well as a comparison with OMA-based cooperative systems in which PRS among either multiple HD-AF relays or multiple FD-AF relays is employed 8 . In this case, the following system parameters are considered: number of relays K = 1, 2, 3, power allocation factors (a 1 , a 2 ) = (0.7, 0.3) and normalized distance of the links R k → D OMA , d R k DOMA = 0.5.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fig. 8 illustrates the system sum rate versus the transmit SNR, as well as a comparison with OMA-based cooperative systems in which PRS among either multiple HD-AF relays or multiple FD-AF relays is employed 8 . In this case, the following system parameters are considered: number of relays K = 1, 2, 3, power allocation factors (a 1 , a 2 ) = (0.7, 0.3) and normalized distance of the links R k → D OMA , d R k DOMA = 0.5.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…Monte Carlo simulations were provided to validate the accuracy of our formulas. Numerical results showed that an outage floor occurs due to the inherent 8 For both HD-OMA and FD-OMA systems, the network setup consists of one source, K relays, and two destinations, all operating on a TDMA basis, as in the FD-NOMA system considered herein. For the HD-OMA system, the source is assumed to send a message to each destination within one different fading block, which is divided into two time slots (one for the source-relay transmission and one for the relay-destination transmission).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, γ SR =| h SR | 2 γ P /2 and γ RD =| h RD | 2 γ P /2 are the instantaneous received SNRs for the first‐ and second‐hop relaying links, respectively, where h SR and h RD are the corresponding channel coefficients, and γ P is the transmit system SNR. Moreover, due to imperfect stages of interference cancelation at the FD relay, a residual self‐interference (RSI) is considered, which can be modeled as a Rayleigh fading loop back channel, with channel coefficient hRRscriptCscriptNfalse(0,σ2false), such that γ RR =| h RR | 2 γ P /2 is the instantaneous received SNR.…”
Section: Applicationsmentioning
confidence: 99%
“…Another application where the statistics of the ratio of independent squared -RVs are considered is in FD relaying systems. 38,39 Let us consider the system depicted in Figure 3, which illustrates a two-hop FD relaying network composed of three nodes: one single-antenna source (S), one single-antenna destination (D), and one DF relay (R) equipped with one transmit antenna and one receive antenna to operate in FD mode. In this system, it is assumed that the direct link is highly attenuated, thus being neglected.…”
Section: Outage Performance Of Full-duplex Relaying Networkmentioning
confidence: 99%